Fuzzy based intelligent control system for elevator / Mohd Norhaslan Alias - Alias, Mohd Norhaslan (2008)
This paper presents the idea to make elevator more efficient for user. This project call video based intelligent control system in elevator. This idea use video based intelligent control system to control the elevator at all time and fuzzy logic based expert system for controlling signal at an intersection. The video can monitor and capture picture at all level then send to system to control the elevator. Both are using MATLAB toolboxes for image acquisition, image processing and fuzzy logic. In this paper only focus on the rule base fuzzy logic. The main objective for this idea is to help people to minimize the waiting time for waiting elevator and also to find solution for efficient dispatch system. It contains of two system monitory it from the key dispatching and video camera. To make it intelligent, fuzzy logic in the MATLAB is use to create rule for this system. By developing the video based intelligent control system for elevator, the time for waiting elevator can be minimize. The result obtained from fuzzy logic simulation.